Morphology and ecology of the marine dinoflagellate Ostreopsis labens sp. nov. (Dinophyceae) - Faust, M.A.; Morton, S.L.
O. labens sp. nov., is described from three marine habitats: lagoonal water and lagoonal sand from the barrier reef of Belize, and associated with macroalgae from coral reef habitats of Oshigaki and Iriomote Islands, Japan. O. labens was most numerous in sand and less in lagoonal waters, and only a few cells were associated with macroalgae. Ingestion of prey by O. labens occurs through the ventral opening. The behavior of O. labens appears similar to that previously described for Dinophysis species. -from Authors
Keywords: DINOFLAGELLATE; ECOLOGY; HABITAT PREFERENCE; NEW SPECIES; TAXONOMY